rt teaching in São Paulo state educational network: between reproduction and resistance in the “school floor” (Revista Educação, Artes e Inclusão, 2025)
In this article it is presented results from a mastership dissertation concerning six research questions related to Art Teachers in the “school floor” of São Paulo State educational network. In both 2016 and 2017 it was carried out research to data collection by means of field observational research in three distinct School Districts and 15 responses to the semi-structured interview applied in North 1 School District. Both data collection and description were grounded in authors from educational ethnography such as Erickson (1986) and Ezpeleta e Rockwell (1989). The stage of analyses and discussion of the obtained results were carried out with support from concepts formulated by Bourdieu e Passeron (2014), sociology of education researchers. Furthermore, it was considered the information concerning teacher’s working conditions as a significant analysis factor. By means of this research it was possible to identify practices of reproduction and resistance that have been perpetuated in daily school life related to Art subject. Also, it was possible to raise significant factors to the comprehension of the continuity and transformational possibilities of the logics of existence of the Art Teaching in the “school floor”.
Keywords: Art Teaching; Reproduction; Resistance; Teachers; School floor